Community empowerment through biofloc catfish fishery with photovoltaic electrical energy in Sutojayan Village, Malang - Hery Budiyanto; Aries Boedi Setiawan; Pindo Tutuko (Community Empowerment, 2022)
The Community Partnership Program (PKM) for tarpaulin fish pond fisheries using photovoltaic electrical energy sources was carried out in Sutojayan Village, Pakisaji District, Malang Regency. The purpose of the community service is to deal with problems that occur in Sutojayan Village related to food security through the application of appropriate technology. The methods of the activities are: 1) focus group discussions and technology dissemination, 2) construction of biofloc catfish tarpaulin ponds and PLTS, and 3) skills and management training of biofloc catfish and PLTS. The result of this program is an increase in the skills of catfish farming groups in applying the biofloc system, business bookkeeping and processing harvests. In addition, there has also been an increase in catfish yields. Furthermore, this program as established 3 (three) biofloc catfish tarpaulin ponds, a set of PLTS, and a management group.